2023
DOI: 10.1002/bdr2.2171
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary caffeine consumption and risk of birth defects in the National Birth Defects Prevention Study, 1997–2011

Abstract: Background: Caffeine consumption is common during pregnancy, but published associations with birth defects are mixed. We updated estimates of associations between prepregnancy caffeine consumption and 48 specific birth defects from the National Birth Defects Prevention Study (NBDPS) for deliveries from 1997 to 2011.Methods: NBDPS was a large population-based case-control study conducted in 10 U.S. states. We categorized self-reported total dietary caffeine consumption (mg/day) from coffee, tea, soda, and choco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…consumption and birth defects, including transverse limb deficiency (Williford et al, 2023). We observed that the association of caffeine consumption from soda differed between male preterm and female preterm compared with female term births among infants with transverse limb deficiency.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…consumption and birth defects, including transverse limb deficiency (Williford et al, 2023). We observed that the association of caffeine consumption from soda differed between male preterm and female preterm compared with female term births among infants with transverse limb deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Caffeine consumption was identified as an important predictor for sex‐preterm birth status multiple models among infants with transverse limb deficiency (caffeine from soda) or gastroschisis (caffeine from coffee). Previous NBDPS analyses have observed some small, elevated effect estimates between pre‐pregnancy total caffeine consumption and birth defects, including transverse limb deficiency (Williford et al, 2023). We observed that the association of caffeine consumption from soda differed between male preterm and female preterm compared with female term births among infants with transverse limb deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Estes benefícios têm de ser ponderados em função de alguns potenciais riscos associados ao consumo de café, como ansiedade, insônia, cefaleias, tremor e palpitações, sintomas que surgem mais frequentemente como consequência de um consumo de doses mais elevadas de café (O' Keefe et al, 2018;Poole et al, 2017) e muitas vezes resultantes de outros fatores associados ao consumo de café (consumo de tabaco, álcool). Também, mulheres gestantes deverão ter em conta o possível impacto do café no desenvolvimento fetal (Jafari et al, 2022;Williford et al, 2023), nos partos prematuros (L. W. Chen et al, 2016;Greenwood et al, 2014;Z. X. Li et al, 2016;Rhee et al, 2015) e aborto espontâneo (Jafari et al, 2022;Lyngsø et al, 2017) , assim como as questões em aberto sobre o impacto do consumo de café na osteoporose e fraturas associadas (Hallstrom et al, 2013;Johansson et al, 1992;Kiel et al, 1990).…”
Section: Caféo Nutracêutico Mais Efetivo?unclassified